Impact of nitrogen and green manure on yield and quality of sweet potato in sandy soil: A Brazilian case study - Fernandes, Adalton Mazetti [UNESP] (2021)
A field experiment was conducted to evaluate the effects of mineral N rates on the yield, morphological traits, quality, and mineral content of the storage roots of sweet potato grown after different green manure sources. Treatments included the application of N at four rates (0, 50, 100, and 200 kg ha−1) to sweet potato grown after the control (indigenous weeds) or the legumes showy crotalaria and velvet bean. PCA revealed that in the treatments with previous showy crotalaria cultivation, there was a low incidence of defects in the storage roots and the storage roots weighed more than they did in the control or in the velvet bean treatments. The current study also showed that legume cultivation only in the previous season was not enough to improve the yield and quality of sweet potato. Therefore, it is necessary to combine previous legume cultivation with the application of 100 or 200 kg N ha−1 in sweet potato to achieve higher levels of yield, quality, and mineral contents, such as Cu, Zn, K, Ca, and Mg, in storage roots. The current research has indicated that future studies should investigate whether the benefits of previous legume cultivation for sweet potato are restricted only to the current growing season.